Efficiency of rat baiting application at Felda Kerteh, Ladang FASSB, Dungun, Terengganu / Che Ahmad Asyraf Che Manan - Che Manan, Che Ahmad Asyraf (Faculty of Plantation and Agrotechnology, 2018)
Rat is the major pest in oil palm plantation in Malaysia. This pest have been reported to attack and feed at part of palm such as germinated seed, apical point, stem, frond, inflorescences and fruit bunch. The effect of this pest can cause decreasing the fresh fruit bunch quality by feeding activity. The significant is on number of bait placement for rat baiting program which is Standard Operation Procedure is apply one bait per palm and recommended method apply 2 bait per palm. The objectives of this research are to determine the efficiency of different rat baiting application system and to compare with the cost. First method is choosing the two study plots that consist of 50 palms. Second, monitoring the rat population at both study plots using CMR technique. Third, control rat population by using rat baiting program with different treatment. Last, analyzed the data used test statistic One Way ANOVA with p < 0.05 using SPSS application. The farmer can use this information as tool for decision making in their estate management. In this study, the standard operation procedure of FELDA was use in rat baiting application and also the rat bait, BUTIK S, product of FELDA. Based on the result, there are no different between Standard Operation Procedure and recommended method. The comparison elements are number of cycle, bait percentages, total bait, labor and rat bait cost and total cost.